Peningkatan Tanggung Jawab Belajar Siswa Melalui Bimbingan Kelompok dengan Teknik Behavior Contract - Apriana, Apriana; Rahmaniah, Ulya; Al Falah, Fajar; Luya, Dionisia; Hendrik, Hendrik (Universitas Palangka Raya, 2025)
This study aimed to examine the effectiveness of group guidance services using the behavior contract technique in improving learning responsibility attitudes among eighth-grade students at SMP Negeri 22 Pontianak. The study employed a two-cycle guidance and counseling action research approach. Data were collected through interviews, observations, and psychological scales. Initial findings indicated that most students’ learning responsibility was in the “moderate” to “low” category. Following the intervention, there was a significant increase in the average score across all indicators, from 49.64% to 78.01%. The highest improvement occurred in the ability to independently choose learning activities, increasing from 50.05% to 93.02%. Observations also recorded an 18% increase in student participation in group guidance sessions. These findings support the hypothesis that the behavior contract technique is effective in enhancing students' learning responsibility within group guidance services. It is recommended that this intervention be applied continuously as part of character education strategies in schools.